Agente único versus combinação de agentes quimioterápicos durante a radioterapia pré-operatória para o tratamento do câncer de reto ressecável: revisão sistemática de ensaios clínicos randomizados - Resende, Heloisa Magda [UNIFESP] (2016)
Introduction: Colorectal cancer represents the third more common neoplasms and acconts for 49.190 deaths for year in the United States. Almost two-thirds of the large intestine tumors are the colon and a third is about the rectum, including anus. Surgery is curative basis of the treatment of rectal cancer. Total mesorectal excision reduces the local recurrence rate, improving the prognosis, but a lot of investment in research has been done to improve the overall results, which are very impacted by still high relapse rates in the distance. Currently rectal cancer is covered with neoadjuvant radiotherapy and chemotherapy fluoropyrimidine-based, followed by surgery, however the distance the recurrence rate is around 30%. chemotherapy regimens in combination of two drugs, similar to what has been used in metastatic and adjuvant therapy have improved the prognosis and have been tested in neoadjuvant character. Objectives: To compare outcomes of patients (overall survival, disease-free survival, and toxicity) between two chemotherapy regimens for patients with rectal cancer stage II and III will receive neoadjuvant treatment with radiotherapy and chemotherapy. Interventions were radiotherapy, fluoropyrimidine and additional drugs, excluding biological agents. The control arm was radiotherapy and chemotherapy with a single agent (fluoropyrimidine) SEARCH STRATEGY: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), EMBASE, MEDLINE and LILACS (last search onSeptember 2014). Completed searching through lists of references, record of "clinical trials" and manual search for relevant papers. There was no language restriction. SELECTION CRITERIA: Randomised controlled trials (RCTs) comparing single-agent chemotherapy (fluoropyrimidine) versus the combination of chemotherapeutic agents (fluoropyrimidine more other agent including but not limited to oxaliplatin) during the pre-operative treatment in patients with rectal unresectable cancer . Collection and analysis of data: Two reviewers (HMR, EMKS) independently extracted data and assessed the quality of RCT. When necessary we request additional information and clarifications to the authors about the published data. Main results: Four RCTs were included totaling 3875 patients with resectable rectal cancer. RCTs were classified between low to moderate risk of bias. In the preoperative period the participants of these RCTs were randomized to receive chemotherapy and radiotherapy both with fluoropyrimidine or a combination of agents (fluoropyrimidine and a second agent). The only study that has reported data of overall survival and progression-free found no differences between the groups compared. For complete pathological response (ypCR) there was a statistically significant difference favoring the experimental group OR = 1.23 (95% CI: 1:04, 1:46), but there were also significantly more acute toxicity in this arm OR = 2.07 (95% CI: 1.31, 3.27). The control group had greater adherence to treatment radiotherapy and chemotherapy, OR = 0:32 (95% CI: 12:14, 0.75) and OR = 0:24 (95% CI: 0.07 to 0.77), respectively. There was no difference between groups with respect to mortality within 60 days, postoperative morbidity, resection margin, abdominal-perineal resection and Hartmann procedure. AUTHORS 'CONCLUSIONS: There is low quality evidence that patients with resectable rectal cancer who receive combination chemotherapy agents preoperatively have no benefit in overall survival and progression-free. There is high quality evidence that combination of chemotherapeutic agents with oxaliplatin can improve local tumor control in these patients, but the regime also cause greater toxicity. Therefore the existing evidence to date does not support the use of oxaliplatin in this context. The publications of more progress in studies of survival data will contribute to further analysis.